Ecological Education in Socialist Society - Juodagalvis, Jonas (Problemos, 1984)
The solution of ecological problems, as the author sees it, is conditioned by the character of economic and socio-political relations of society. Socialism creates favourable objective preconditions for developing ecological culture. In the article greatest attention is given to the analysis of the influence of subjective factors of social development on the solution of ecological problems. A system of ecological education is also outlined.